Phát hiện loại thực vật thuộc chi Wrightia (Apocynaceae) cho chất nhuộm màu chàm ở Lâm Đồng - Hoàng, Thị Bình (Trường Đại học Đà Lạt, 2012)
In Lam Dong province, there are a plant specie having indigo dye in Apoaceae family: Wrightia dubia (Sims.) Spreng. This research was shown distributed location, and indigo content in this plant specie